2020
DOI: 10.1200/jco.2020.38.18_suppl.lba110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of COVID-19 on patients with cancer: Data from the COVID-19 and Cancer Consortium (CCC19).

Abstract: LBA110 Background: There are limited data on COVID-19 in patients with cancer. We characterize the outcomes of patients with cancer and COVID-19 and identify potential prognostic factors. Methods: The COVID-19 and Cancer Consortium (CCC19) cohort study includes patients with active or prior hematologic or invasive solid malignancies reported across academic and community sites. Results: We included 1,018 cases accrued March-April 2020. Median age was 66 years (range, 18-90). Breast (20%) and prostate (16%) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 0 publications
3
24
0
1
Order By: Relevance
“…The last ASCO annual meeting hosted a special session on cancer and COVID-19 pandemic. In this session data from the thoracic cancers international COVID-19 collaboration (TERAVOLT) registry and from the COVID-19 and cancer consortium registry (CCC-19) were presented [19][20][21]. The TERAVOLT study focused on thoracic Patient's condition is stable enough that services can be delayed for the duration of the COVID-19 pandemic and/or the intervention is no priority based on the magnitude of benefit malignancies and recruited 400 patients, mainly from Italy, with either confirmed COVID-19 infection or clinically/radiologically suspected infection [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last ASCO annual meeting hosted a special session on cancer and COVID-19 pandemic. In this session data from the thoracic cancers international COVID-19 collaboration (TERAVOLT) registry and from the COVID-19 and cancer consortium registry (CCC-19) were presented [19][20][21]. The TERAVOLT study focused on thoracic Patient's condition is stable enough that services can be delayed for the duration of the COVID-19 pandemic and/or the intervention is no priority based on the magnitude of benefit malignancies and recruited 400 patients, mainly from Italy, with either confirmed COVID-19 infection or clinically/radiologically suspected infection [19].…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported a mortality rate of 35% with a median follow-up of 33 days. The CCC-19 study reported data on 928 confirmed COVID-19 positive patients, mostly from USA, with various types of cancers [ 20 , 21 ]. The most prevalent malignancies were breast (21%) and prostate cancer (16%), while the mortality rate was 13% with a median follow-up of 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective chart review of 1878 patients with COVID-19 at a Spanish hospital found that 17 had lung cancer, of whom 9 died [24]. Among 1018 patients with both COVID-19 and cancer, independent factors associated with increased 30-day mortality were age, male sex, former smoking, and worse Eastern Cooperative Oncology Group (ECOG) performance status [25].…”
Section: Do Patients With Covid-19 and Underlying Malignancy Have Wormentioning
confidence: 99%
“…Among 1018 patients with both COVID-19 and cancer, independent factors associated with increased 30-day mortality were age, male sex, former smoking, and worse Eastern Cooperative Oncology Group (ECOG) performance status [ 25 ].…”
Section: Do Patients With Covid-19 and Underlying Malignancy Have Wormentioning
confidence: 99%
“…However, the limited data have not led to evidence‐based recommendations. Evidence suggests that COVID‐19 diffusion in patients with cancer is not as prominent as expected; however, mortality seems to be higher than that reported for the general population and correlates with general risk factors as well as those unique to patients with cancer 8‐12 . Indeed, other comorbidities (eg, cardiovascular disease, diabetes, chronic obstructive pulmonary disease) correlate with a higher risk of infection and severe events 13 …”
Section: Introductionmentioning
confidence: 99%